Impact of the Physical Activity on Bullying - Méndez, Inmaculada; Ruiz-Esteban, Cecilia; Ortega, Enrique (Frontiers in Psychology, 2019)
Relationship problems among school children can lead to bullying situations. In this regard, it should be noted that, among healthy lifestyle habits, sports practice (non-competitive) promotes responsibility and improves coexistence. The objective of the present study was to analyze the incidence of the frequency of practice of healthy physical activity on the risks of students directly involved in school bullying (harasser and victim) by gender. The participants of the study were 1,248 students of Compulsory Secondary Education with ages between 11 and 18 (M = 14.42, Dt = 1.43), being 50.8% males. The results of the study indicated that students who practiced physical activity in the recommended frequency rated as healthy, at least four or more times per week, had higher values in the indicators of aggressiveness than students who practiced with a lower frequency, appreciating a greater relationship between both variables in male rather than in female students. The study will make progress in preventive and intervention programs whose central axis is the promotion of physical activity and healthy sport (non-competitive) among students involved in situations of bullying. Likewise, teacher training in the recognition of bullying is considered a priority, providing them with guidelines for action.